A Comparison of Two Peripheral Nerve Blocks Combined With General Anesthesia in Elderly Patients Undergoing Arthroplasty for Hip Fractures: A Pilot Randomized Controlled Trial - Zhang, Qingfu; Ling, Ming; Wang, Xintao; Cui, Derong (Frontiers in Surgery, 2022)
Background Combined anesthesia can be a promising option for hip surgery when neuraxial anesthesia is contraindicated. Lumbar and sacral plexus blocks, and femoral nerve and lateral femoral cutaneous (LFC) nerve blocks in combination with general anesthesia (GA) are commonly used in elderly patients undergoing arthroplasty for hip fracture surgery. However, no study has compared these two anesthetic strategies in the perioperative period. Methods Forty-one elderly patients scheduled for arthroplasty for hip fracture surgery were randomized into group A (n=20) and group B (n=21). Group A received femoral nerve block, LFC nerve blocks and GA, and group B received lumbar plexus block, sacral plexus block and GA. Primary outcomes were incidences of hemodynamic events and changes in blood pressure and heart rate. Secondary outcomes included time and drug consumption, infusion and bleeding volume, eyes opening time after surgery, and postoperative quality recovery rate. Results Compared with group B, group A showed lower incidence of intraoperative hypotension (P<0.001), higher blood pressure (including mean arterial pressure, systolic and diastolic blood pressure) following induction (IN), and higher heart rate from mid-surgery. Time required for nerve blockade (P<0.001) and ephedrine consumption was significantly shorter in group A (P<0.001), while sufentanil consumption was higher as compared to Group B (P=0.002). No significant differences in other intraoperative parameters and postoperative quality recovery rate were reported during the observation. Conclusion Our pilot data indicates that compared with lumbar and sacral plexus blocks, femoral nerve and LFC nerve blocks may provide more stable intraoperative hemodynamics and a comparable postoperative recovery for elderly patients undergoing arthroplasty for hip-fracture under GA. Further studies with larger sample size are needed to derive stronger evidence.